Development of E-Worksheet Inquiry-Flipped Classroom on Chemical Equilibrium Material To Improve Students' Analytical Thinking Skills - Maulidiya, Lailatul; Novita, Dian (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
One of the skills that students must have in the 21st century is analytical thinking skills. Learning media that can support this is needed to facilitate learning and practice analytical thinking skills. One learning media that can be used is an electronic student activity sheet (e-worksheet). This research aims to produce a product in the form of an e-worksheet suitable for use to improve students' analytical thinking skills on chemical equilibrium material. The feasibility of the e-worksheet is reviewed on its validity, effectiveness, and practicality. The method used is the research and development of 4D models consisting of definition, design, development, and deployment. This research was limited to the development stage by conducting a limited trial on students in grades XI-8 of SMAN 7 Surabaya who had studied chemical equilibrium material. The data collection technique of this research uses questionnaire, observation, and test methods. The research instruments used in this study include study sheets, validation sheets, student response questionnaire sheets, observation sheets, and test sheets. This study was analyzed using the N-gain test and the Wilcoxon test. The results of the validation of the e-worksheet from the aspects of content validity and construct validity obtained a mode of 4 so that it can be declared very valid for use. The results of the student response questionnaire reached an average of 98% positive responses in the very practical category. The results of the analysis of pretest and post-test data were obtained to improve analytical thinking skills, which was shown by 80% of students receiving an N-gain score of ≥ 0.7 with a high category and based on the Wilcoxon test, a P-Value value of 0.000 (< 0.05) was obtained which stated that there was a significant difference between the pretest and posttest scores Learners. From the results of the N-Gain analysis and the Wilcoxon Test, the e-worksheet was declared effective. It was concluded that the flipped classroom inquiry e-worksheet on chemical equilibrium material is suitable for training students' analytical thinking skills.